Pengaruh Kinerja SDM Dan Efektifitas CBIS Terhadap Daya Saing - Agung Setiawan (RJOCS (Riau Journal of Computer Science), 2016)
This study will analyze the relationship between the performance of human resources and computer-based information systems with competitiveness. The relationship between thethree is moderate and strong, it can be seen from the correlation between the performance of human resources with the effectiveness of computer based information system by 0441 or are being, the relationship between the performance of human resources with competitiveness by 0547 or are currently, the relationship between the effectiveness of information systems based computer with competitiveness by 0695 or strong relationship between the performance of human resources and computer-based information systems along with a computer-based information system competitiveness by 0745 or stronger. In addition to testing the relationship among the three, this study also examines the significance level of the three. In a significant test, it turns out the relationship between the performance of human resources and informationsystems based on competitiveness, either individually or together turned out to be highly significant relationship. This indicates that human resources and computer-based informationsystems are closely related to competitiveness.